X2+y2-6+10y-2=0

Simple and best practice solution for X2+y2-6+10y-2=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X2+y2-6+10y-2=0 equation:



X2+X2-6+10X-2=0
We add all the numbers together, and all the variables
2X^2+10X-8=0
a = 2; b = 10; c = -8;
Δ = b2-4ac
Δ = 102-4·2·(-8)
Δ = 164
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{164}=\sqrt{4*41}=\sqrt{4}*\sqrt{41}=2\sqrt{41}$
$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(10)-2\sqrt{41}}{2*2}=\frac{-10-2\sqrt{41}}{4} $
$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(10)+2\sqrt{41}}{2*2}=\frac{-10+2\sqrt{41}}{4} $

See similar equations:

| 8x+3=63-4x | | 15x-3x-18+8=26 | | 11=6+5/y | | 32/60=6/x | | 3(a+2)=-12 | | 3(a=2)=-12 | | 3x÷5+8=x | | 3(x-5)=6  | | 1/4(3x+1)=1/3(4x-1) | | 17x-181=10 | | x*1.1=150 | | 2c+15=-9 | | 9y+12=6y=48 | | w/2+(-0.4)=0.5 | | 3(x-1)+11=7 | | X^2+Y^2+z^2=289 | | 3b=336+11b | | 20-0.24x=14 | | 1/6-p=2/3 | | 5m-7=10-4m | | 64=g-10 | | -12=-5.3+a | | 2y+3=21(y=-9) | | 2x2-8x-64=0 | | 14=-8k-3+1* | | 5500=n+2600 | | 2y+3=6+y | | 57=5x-3(7x+13) | | |2x-8|=x+1 | | -11(x+26)-27(x+26=15x-15 | | (x/4)-5=-9 | | 6^x^2-3x-7=216 |

Equations solver categories